The Role of the Sasi Tradition in Supporting Environmental Conservation and Developing Character Love the Environment - Bolan, Nurhalifah; Juniartin, Juniartin (International Journal of Education, Information Technology, and Others, 2024)
Indonesia, as the owner of the largest biodiversity, also possesses various local wisdoms that contain profound meanings. The sasi tradition is a prohibition on the community from continuously harvesting natural resources at any time, but rather at specific intervals, to allow environmental recovery. Sasi, as practiced within communities, serves to maintain the quality and sustainability of biological resources, and this resource management is overseen by traditional institutions such as rajas, heads of soa, saniri, kewang, and marinyo. Sasi can also be understood as a tradition aimed primarily at ensuring the continuity and balance of natural resources. This tradition is a cultural value widely practiced among indigenous communities in Maluku, and is found across all Maluku islands, including Halmahera, Ternate, Buru, Seram, Ambon, the Lease Islands, Watubela, Banda, the Aru Islands, the Southwest Islands, and the western part of Southeast Maluku. Therefore, this scientific paper aims to examine the role of the sasi tradition in supporting environmental conservation and fostering a love for nature. The method used is a literature review, involving reading, studying, analyzing, and reviewing literature related to the role of sasi in supporting environmental conservation and fostering environmental awareness. The findings of this study indicate that the sasi tradition strongly supports environmental conservation and can also foster a love for nature.